2017
DOI: 10.1016/j.memsci.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polydopamine deposition conditions on hydraulic permeability, sieving coefficients, pore size and pore size distribution for a polysulfone ultrafiltration membrane

Abstract: Membrane surface modification with polydopamine (PDA) coatings can reduce fouling in oily water filtration due, at least in part, to enhanced surface hydrophilicity. In this study, polysulfone (PSf) UF membranes were coated with PDA. PDA coating conditions (solution concentration and deposition time) were varied, and the effect of coating conditions on membrane molecular weight cutoff (MWCO) and hydraulic permeability was measured. Membrane MWCO decreased and PDA film thickness increased as initial dopamine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 69 publications
(147 reference statements)
9
63
0
Order By: Relevance
“…The presence of foulants in the feed water leads to deposition and accumulation on the membrane surface and internal pores blocking. For porous membranes like UF, pore size reduction and pore blocking are the major factors influencing the water flux decrease . The decrease of water flux would not only cause inconvenience for practical operation, but also increase the operating costs due to the requirement of membrane cleaning and replacement .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of foulants in the feed water leads to deposition and accumulation on the membrane surface and internal pores blocking. For porous membranes like UF, pore size reduction and pore blocking are the major factors influencing the water flux decrease . The decrease of water flux would not only cause inconvenience for practical operation, but also increase the operating costs due to the requirement of membrane cleaning and replacement .…”
Section: Introductionmentioning
confidence: 99%
“…For porous membranes like UF, pore size reduction and pore blocking are the major factors influencing the water flux decrease. 1,6 The decrease of water flux would not only cause inconvenience for practical operation, but also increase the operating costs due to the requirement of membrane cleaning and replacement. 7,8 Membrane fouling also leads to higher energy needed to keep the membrane performance constant.…”
Section: Introductionmentioning
confidence: 99%
“…However, application of coatings or grafting materials to membrane surfaces may introduce additional mass transfer resistance to the membrane, resulting in reduced pure water permeance [3,7,8]. For porous membranes, the permeance decrease is often due to membrane separation layer thickness increase and pore size reduction or pore blockage caused by surface modification [9,10]. During constant global (i.e., overall) permeate flux filtration, pore blockage or pore size decrease could increase local convective permeate flux through the pores, enhancing the forces responsible for bringing foulants to the membrane surface, thereby increasing fouling [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, severe reductions in membrane pure water permeance due to application of the PDA coating on porous membranes should be minimized to avoid, at fixed global or overall 2 flux, increases in local permeate flux due to pore narrowing or blocking as a result of PDA modification, which could exacerbate fouling [20]. Generally, the pure water permeance of these membranes can be controlled by varying PDA modification conditions such as coating solution concentration and coating time [8,9,17,20]. Since even a minimal application of PDA to the membrane surface can significantly improve surface hydrophilicity, and more substantial applications of PDA have little effect on hydrophilicity, PDA can be used to examine the effect of changing pore size in a hydrophilic membrane.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated that at less scan cycles (such as 2 scan cycles) PDA film was uncontrolled which exhibited high permeability to cationic and anionic species while at more scan cycles (such as 15 scan cycles) hindered cationic and anionic species. Probably reasons were that thickness , pore size and structures of PDA film have been changed before reaching 15 scan cycles. However, the PDA modified electrode electropolymerized for more than 15 cycles was somewhat less sensitive to detect a low concentration dopamine.…”
Section: Resultsmentioning
confidence: 99%